Reliability analysis of riverbank stability accounting for the intrinsic variability of unsaturated soil parameters. (September 2020) - Gottardi, Guido; Gragnano, Carmine G.; Ranalli, Marco; Tonni, Laura
Highlights: Probabilistic stability analyses of riverbank slopes are discussed. Time dependent hydraulic loads and unsaturated soil conditions are considered. Uncertainties in soil mechanical and hydraulic parameters are taken into account. The simplified uncertainty propagation method Point Estimate Method is adopted. Failure probability is underestimated if hydraulic parameter variability is neglected. Abstract: The paper presents a probabilistic study aimed at investigating the role of the soil hydraulic response on the stability of existing river embankments, for which the uncertainty and the inherent variability of geotechnical and hydraulic properties are typically greater when compared to new flood defence structures. The study has been carried out with reference to a specific, thoroughly investigated 20 m-long segment of the river Secchia banks (northern Italy), which experienced a catastrophic sudden failure after a period of intense rainfall, in January 2014. By taking such well-documented case as a base, the proposed probabilistic analyses consider three key aspects, typically disregarded in routine risk assessment procedures: i) transient seepage flow through earth structures due to time dependent hydraulic loads, ii) unsaturated conditions of soils forming the river embankment, iii) uncertainty of the soil model parameters, with special emphasis placed on the impact of intrinsic variability of unsaturated soil parameters. The numerical results, obtained from the application of the Point Estimate Method, allow identifying the crucial role of suction distribution on the probability of failure of the riverbank slopes and clearly show that such probability can be significantly underestimated when the variability of hydraulic parameters is neglected.